Comparison of Therapeutic Effects of Laparoscopic and Open Operation for Congenital Choledochal Cysts in Adults - Yuan Liu; Xu Yao; Shuqiang Li; Wenhan Liu; Lei Liu; Jingang Liu (Gastroenterology Research and Practice)
Background. Laparoscopic cyst excision and Roux-en-Y hepaticojejunostomy for treating congenital choledochal cysts (CCCs) have proved to be efficacious in children. Its safety and efficacy in adult patients remain unknown. The purpose of this study was to determine whether the laparoscopic procedure was feasible and safe in adult patients. Methods. We reviewed 35 patients who underwent laparoscopic operation (laparoscopic group) and 39 patients who underwent an open procedure (open group). The operative time, intraoperative blood loss, time until bowel motion recovery, duration of drainage, postoperative stay, time until resumption of diet, postoperative complications, and perioperative laboratory values were recorded and analyzed in both groups. Results. The operative time was longer in the laparoscopic group and decreased significantly with accumulating surgical experience (P<0.01). The mean intraoperative blood loss was significantly lower in the laparoscopic group (P<0.01). The time until bowel peristalsis recovery, time until resumption of diet, abdominal drainage, and postoperative stay were significantly shorter in the laparoscopic group (P<0.01). The postoperative complication rate was not higher in the laparoscopic group than in the open group (P>0.05). Conclusions. Laparoscopic cyst excision and hepaticojejunostomy are a feasible, effective, and safe method for treating CCCs in adult patients.